Direct effect of melatonin on Syrian Hamster testes: Mel1a receptors, inhibition on androgen production, and interaction with the local corticotropin-releasing hormone (CRH) system - Frungieri, Monica Beatriz (2005)
Besides the hypothalamus and pituitary, melatonin action at the testicular level has been recently suggested. Therefore, we investigated in the Syrian hamster, a well-characterized seasonal breeder, melatonin action on Leydig cells, testicular expression of melatonergic receptors, and possible interactions between melatonin receptors and the previously identified testicular serotoninergic and CRH systems. In isolated Leydig cells from active testes of adult hamsters kept in a long-day (14 h light, 10 h dark) photoperiod and from regressed testes of adult animals exposed to a short-day photoperiod during 16 wk (6 h light, 18 h dark), melatonin significantly reduced human chorionic gonadotropin-stimulated production of cAMP and the main androgens: testosterone and androstane-3alpha,17beta-diol, respectively, and decreased the expression of steroidogenic acute regulatory protein, P450 side chain cleavage, 3beta-hydroxysteroid dehydrogenase and 17beta-hydroxysteroid dehydrogenase. In Leydig cells exposed to a short-day photoperiod during 16 wk, melatonin stimulated the conversion of testosterone into 5alpha-reduced androgens by inducing 5alpha-reductase isoform 1, and controlled androstane-3alpha,17beta-diol production by inhibiting 3alpha-hydroxysteroid dehydrogenase expression. Melatonin subtype (mel1a) receptors were detected in Leydig cells. Although the local serotonin system did not mediate melatonin action on androgen production, melatonergic effect on steroidogenesis involved the interaction between mel1a receptors and the inhibitory CRH system. Moreover, melatonin significantly increased CRH mRNA levels and production in hamster Leydig cells expressing CRH subtype 1 receptors. Our studies indicate that melatonin may act as a local inhibitor of human chorionic gonadotropin-stimulated cAMP and androgen production through mel1a receptors, down-regulation of steroidogenic acute regulatory protein, and key steroidogenic enzymes expression and its interaction with the local CRH system.